The Principle of Simplicity in Corporate Income Tax In Indonesia - Husen, Yusuf; Wantu, Fence M.; Kasim, Nur Mohamad (Damhil Law Journal, 2021)
This study aims to find out the simplicity of corporate income tax collection regulation in Indonesia's general provisions of taxation. This study uses normative research methods using a legal approach. This study was reviewed with primary and secondary legal material sources. The data analysis techniques used are the analysis of legal interpretation or interpretation of the law. The results showed that Law No. 36 of 2008 on the Fourth Amendment to Law No. 7 of 1983 on Income Tax regulates corporate tax and permanent establishment using a single rate with a tax collection percentage of 22%. This arrangement makes tax collection simpler because it uses only one layer of the same rate and makes corporate income tax in Indonesia more competitive.